The determinants of TCFD reporting: A focus on the Italian context - Salvatore Principale; Simone Pizzi (Administrative Sciences, 2023)
The recommendations of the Task Force on Climate Change Disclosure (TCFD) represent fundamental guidelines for managing climate-change-related risks. Indeed, the TCFD outlines good practices for integrated risk management as well as aims to protect investors and stakeholders through a more transparent and complete disclosure on the subject. However, the adoption of the recommendations was slow and differentiated between countries. The study aims to analyze the determinants that have influenced the voluntary choice of companies to adopt the TCFD recommendations. Using a logistic regression on a sample of Italian public interest entities, the results show that the size of the board, the integration of ESG risks, and the size of the company are variables that influenced the managers' decision to adopt the guidelines.
Keywords: 350; climate accounting; Directive 2014/95/EU; sustainability reporting; Task Force on Climate-related Financial Disclosures (TCFD)